If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 6y = 6 Solving 9 + 6y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 6y = 6 + -9 Combine like terms: 9 + -9 = 0 0 + 6y = 6 + -9 6y = 6 + -9 Combine like terms: 6 + -9 = -3 6y = -3 Divide each side by '6'. y = -0.5 Simplifying y = -0.5
| 13(d+6)=3(d-8)+10d | | 4x+16x= | | 0.005(x-5000)+0.06x=1620 | | 4n=4(40-n) | | 3r=-6r+27 | | 3(g-4)-8=-19 | | 105=5(-3-3x) | | 4w-18=12w+14 | | S+12=7 | | 13+8x=45 | | 21s-24=-20 | | 4v+6=2v-4 | | -8(k-2)-6(k-8)=22 | | 5(w+9)=49 | | 3x-5.46=-3.87 | | 2x+18=-2y+12 | | 5.5-8.1=x | | ax+28x= | | -10+1=q | | -5t-2(-5t+10)=100 | | -8(-8-6)=-6-22 | | 4x-5=5x-7 | | 12=-6z-6 | | x^3+13=-14 | | -5(9+a)=10 | | 44=t-20 | | 383=8x+7 | | 9=4(5-a) | | 10x+6=6x-3 | | -1(x+8)+9=7x+1-8x | | 2z=19.9 | | -11-5=6(5+4) |